2009
DOI: 10.1063/1.3167823
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal magnetic-field dependence of Hall coefficient in InN epilayers

Abstract: We report on magnetic-field dependences of Hall coefficient and resistivity for InN films grown by plasma-assisted molecular beam epitaxy. The Hall coefficient rises with the magnetic field. This anomalous behavior is discussed in terms of the presence of highly conducting inhomogeneities in the films. According to the magnetic field and temperature dependences of the film resistivity, the inhomogeneities are attributed to metallic indium nanoparticles formed presumably around extended defects within the InN e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0
3

Year Published

2010
2010
2018
2018

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 14 publications
0
9
0
3
Order By: Relevance
“…Recently it has been shown that presence of the In inclusions in InN films results in the abnormal magnetic-field dependence of the Hall coefficient RH and strong magnetoresistance effect [11,12]. In this case, the electron concentration and mobility of the InN semiconductor matrix can be determined only from fitting the magnetic-field dependence of R H in the frames of the model taking into account presence of the highly conductive In nanoparticles [11]. R H has been found to increase with B for all the investigated InN films.…”
Section: Resultsmentioning
confidence: 99%
“…Recently it has been shown that presence of the In inclusions in InN films results in the abnormal magnetic-field dependence of the Hall coefficient RH and strong magnetoresistance effect [11,12]. In this case, the electron concentration and mobility of the InN semiconductor matrix can be determined only from fitting the magnetic-field dependence of R H in the frames of the model taking into account presence of the highly conductive In nanoparticles [11]. R H has been found to increase with B for all the investigated InN films.…”
Section: Resultsmentioning
confidence: 99%
“…учитывающей влияние кластеров In на электрические свойства образцов (см. рисунок) [11,14]. Помимо x на основе данной аппроксимации также Т.А.…”
Section: 3unclassified
“…Данный предельный случай был выбран в связи с тем, что, хотя для твердых растворов In x Ga 1−x N при 0.4 x < 1 и наблюдаются аналогичные эффекты, связанные с кластерами In [8], их влияние может быть замаскировано дополнительными явлениями, обусловленными фазовым распадом твердого раствора и параллельной проводимостью областей InGaN с низким содержанием In. Процентное содержание металлических включений In в InN определялось исходя из аппрок-симации магнитополевых зависимостей модуля коэффициента Холла, вид которых, как было показано ранее [11], зависит от транспортных параметров полупроводниковой матрицы InN и количества кластеров In.…”
unclassified
See 1 more Smart Citation
“…Importantly, the size of the bright intensity spot in the cavity center (<0.5 μm) is comparable with the wavelength inside InN (1/3 free‐space wavelength of emission). We should exclude the diffusion of carriers as an important factor for this phenomenon because of low carrier mobility in InN (). The increased surface recombination should be also rejected, because InN‐based structures possess a surface electron accumulation layer, whose characteristics such as the surface‐state density and surface Fermi level are weakly dependent on temperature ().…”
Section: Quasi‐wgms In the Cup‐cavitiesmentioning
confidence: 99%